Determination of Manidipine Hydrochloride in Tablets by High-Performance Liquid Chromatography - Pamanivong, Chansapha; Tatong, Walapa (Journal of Health Research, 2017)
A High Performance Liquid Chromatography (HPLC) method was developed to determination Manidipine hydrochloride in tablets. The system comprises of a Symmetry C-18 (4.6 x 150 mm, 3.5 µm i.d.) as stationary phase, a 45 : 55 mixture of ammonium formate buffer (25 mM, pH 3.1) as mobile phase, flow rate 0.7 ml/min, column temperature at 30oC and detection wavelength at 230 nm. Furthermore, the method was studied stress degradation which carried out under the conditions of hydrolysis (1N NaOH and 1N HCl), oxidation (30% H2O2), photolysis (UV 254 nm) and thermal degradation (60oC) were investigated. Validation of the optimum condition was performed on commercially Manidipine hydrochloride tablet formulations. Validation on the method was assessed from the specificity, linearity and range, precision, accuracy, limit of detection and quantification, stability of solution and system suitability. The linear ranges of 50 - 150 µg/ml was found for Manidipine hydrochloride. The system and method precision calculated from the relative standard deviation was less than 2%. The percentage recovery on accuracy was 99.42%, the limit of detection and quantification were 0.14 and 0.43 µg/ml, respectively. The purposed method was successfully applied to the direct determination of Manidipine hydrochloride in tablet formulations. The results were statistically compared with those of the reference method (Japanese Pharmacopoeia, 15th edition, Supplement I).